Infrared spectroscopy and electroreflectance in the region of fundamental optical transition E₀ of heavily doped n-GaAs (100) - Gentsar, P.O.; Vlasenko, O.I.; Vuichyk, M.V.; Stronski, O.V. (Functional Materials, 2009)
Studied were the reflection spectra of dynamically chemically etched n-GaAs (100) single crystals with electron concentration of 10¹⁸ to 5·10¹⁸ cm⁻³ in the 1.4-25 μm range as well as the electroreflection ones in 1.3-1.6 eV range using electrolytic method. The values of physical parameters and parameters in the space charge region of subsurface layer of the investigated material have been obtained: electron concentration N, plasma frequency ωp, relaxation time of free carriers over the pulse τp, energies of optical transitions E₀(Г₈ᵥ-Г₆c), electrooptical energy hθ, surface electric field Fs, phenomenological broadening parameter Г, energy relaxation time τ, the wave function oscillation durability of quantum-mechanical particle λᴋғ with the reduced effective mass μ at a given surface electric field Fs. The energy diagram of the chemico-dynamically etched n-GaAs (100) surface has been found to include an extreme. The presence of such extreme is explained by zero value of the electron wave function on the surface and/or the structure gettering of the free carriers. Досліджено спектри відбивання у діапазоні 1,4-25 мкм та спектри електровідбивання з використанням електролітичної методики у спектральному діапазоні 1,3-1,6 еВ монокристалів n-GaAs (100) після хіміко-динамічного травлення з концентрацією електронів 10¹⁸-5·10¹⁸ см⁻³. Отримано значення фізичних параметрів та параметрів в області просторового заряду приповерхневого шару матеріалу: концентрації електронів N, плазмові частоти ωp час релаксації вільних носіїв за імпульсом τp, енергії оптичних переходів E₀(Г₈ᵥ-Г₆c), електрооптичної енергії hθ, поверхневого електричного поля Fs, феноменологічного параметра уmирення Г, енергетичного часу релаксації !, протяжності осциляції хвильової функції квантово-механічної частинки λᴋғ із приведеною ефективною масою μ при даному поверхневому електричному полі Fs. Виявлено, що енергетична діаграма хіміко-динамічно травленої поверхні n-GaAs (100) містить екстремум. Появу такого екстремума пояснено нульовим значенням хвильової функції електронів на поверхні і (або) зі структурним гетеруванням вільних носіїв. Исследованы спектры отражения в диапазоне 1,4-25 мкм и спектры электроотражения с использованием электролитической методики в спектральном диапазоне 1,3- 1,6 эВ монокристаллов n-GaAs (100) с концентрацией электронов 10¹⁸-5·10¹⁸ см⁻³ после химико-динамического травления. Получены значения физических параметров и параметров в области пространственного заряда приповерхностного слоя материала: концентрации электронов N, плазменные частоты ωp время релаксации свободных носителей по импульсу τp, энергии оптических переходов E₀(Г₈ᵥ-Г₆c), электрооптической энергии hθ, поверхностного электрического поля Fs, феноменологического параметра уширения Г, энергетического времени релаксации t, протяженности осцилляции волновой функции квантово-механической частицы λᴋғ с приведенной эффективной массой μ при данном поверхностном электрическом поле Fs. Выявлено, что энергетическая диаграмма химико-динамически травленой поверхности n-GaAs (100) имеет экстремум. Появление такого экстремума объяснено нулевым значением волновой функции электронов на поверхности и (или) со структурным геттерированием свободных носителей.